Universal Health Coverage - Osoro, Alfred A.; Atitwa, Edwine B.; Moturi, John K. (My University, 2020)
Universal Health Coverage has attracted global attention as an ideal vehicle that will drive health care services to the individuals, families, and communities globally. Good health systems are capable of serving the needs of entire populations, including the availability of infrastructure, human resources, health technologies, and medicines. This study seeks to identify the barriers and challenges which have hindered the provision of basic health care to communities and suggest ways of addressing some of them. Literature search reviewed 40 materials which were more relevant. Results revealed that there have been disparities in the provision of healthcare. Challenges in service provision include; lack of political commitment, weak health system resulting from limited financial allocation and poor leadership, lack of adequate number of skilled human resources, equipment and supplies and poor infrastructures. For UHC to be successful, an effective and well-functioning Primary Health Care (PHC) system is essential. Thus health systems can be strengthened through financial allocation; training of skilled and well-motivated healthcare workers. Also provision of right equipment and supplies, equity in resource distribution, improvement of infrastructures to meet the needs of the people is fundamental.
Keywords: universal health coverage; primary health care; skilled human resources